Testing the Technology Acceptance Model (TAM) and the Use of Artificial Intelligence in Cryptocurrency Investment Decision-Making by Retail Investors - Liya Alimatussakdiah Munawarah; I Nyoman Nugraha Ardana Putra (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to analyze the effect of Perceived Usefulness and Perceived Ease of Use on the use of Artificial Intelligence and its impact on cryptocurrency investment decision-making among retail investors in Indonesia. This research employs a quantitative approach using a survey method by distributing questionnaires to 123 respondents selected through purposive sampling. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results show that Perceived Usefulness and Perceived Ease of Use have a positive and significant effect on the use of Artificial Intelligence. Furthermore, the use of Artificial Intelligence also has a positive and significant impact on investment decision-making. Both variables also have a direct significant effect on investment decisions, and the use of Artificial Intelligence is proven to mediate the relationship between user perceptions and investment decisions.